UPAYA PEMERINTAH DAERAH DALAM MENUMBUHKAN EKONOMI KREATIF MASYARAKAT SUMATERA UTARA - Tripriyono, Agus (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
The study aims to describe the creative economy of the people of North Sumatra, map the problems and analyze the efforts of the Regional Government in growing the creative economy of the people of North Sumatra. This research uses a narrative approach and is analyzed qualitatively. The research was conducted in Deli Serdang, Tebing Tinggi, Binjai, and Karo. The informants of the study consisted of: Industry and Trade or other designations; Office of Cooperatives, Micro, Small and Medium Enterprises (MSMEs) or other designations; Tourism Office or other designations. Data collection is carried out through interviews, observations, documentation, and discussions. North Sumatra has 16 creative economy subsectors spread across 33 regencies/cities in North Sumatra Province. Four creative economy subsectors that have the largest number of businesses/industries, namely: Culinary (74.45%); Fashion (15.66%); Craft (6.85%); Publishing (1.35%), and the rest is below 1%. The creative economy in North Sumatra does not grow and develop evenly. The problems in growing the creative economy of the people of North Sumatra are related to: human resources, raw materials, capital/financing, institutions, products/products/works, infrastructure, and marketing. The efforts and policies of the Regional Government in developing the creative economy of the people of North Sumatra, namely: training, guidance, mentoring, promotion and marketing, publications, development of information systems, assessment and formulation of policies, appreciation to the creative community, socialization of IPR/PATEN, development/revitalization/facilitation of infrastructure, counseling, business meetings, establishment of IKM centers.